AST Cutting Edge of Transplantation 2013 Meeting Report: A Comprehensive Look at B Cells and Antibodies in Transplantation. Issue 3 (24th January 2014) - Mengel, M.; Chong, A.; Rothstein, D. M.; Zorn, E.; Maltzman, J. S.
<x xml:space="preserve">Abstract</x> Antibody‐mediated rejection (ABMR) represents a significant clinical challenge for solid organ transplantation. Mechanistic understanding of ABMR is incomplete and diagnostic accuracy for ABMR is limited, and as a result, targeted treatment remains elusive and new treatment modalities are difficult to validate. Three hundred twenty‐six participants from 15 countries met for the first Cutting Edge of Transplantation (CEOT) symposium organized by the American Society of Transplantation (AST) in Chandler, Arizona, February 14–16, 2013. During the 3‐day interactive symposium, presentations, moderated poster sessions and round table discussions addressed cutting edge knowledge of B and plasma cell biology, mechanisms of antibody‐mediated tissue injury, advances and limitations in ABMR diagnostics, as well as current and potential new treatment options for ABMR. The outcome of the meeting identified the following unmet needs for: (a) improved understanding of the regulation of B cell maturation and antibody response to enable targeted therapies; (b) more precise diagnostics of ABMR, including molecular pathology, risk stratification by sensitive antibody testing and monitoring of treatment effects; and (c) innovative multicenter trial designs that enhance observational power, in particular, in assessing synergistic multimodality therapies with reduced toxicities.